Cowshed Design Using Quality Function Deployment (QFD) Method - Diyah Dwi Nugraheni; Hardik Widananto; Andri Haryono Awalokta Kusuma (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
The increase in population and public awareness of the importance of animal protein have also caused increasion of animal protein consumption, especially beef. Therefore, it is necessary to increase beef production by increasing the livestock cattle. Cage condition plays an important role in increasing beef production. The better condition of the cowshed, the greater cow’s health will improve. The QFD method aims to design cowshed based on user desires by translating them into attribute forms. The criteria desired by users for the design of cowshed include: a) There is waste disposal; b) Using brick walls; c) Using wooden poles; d) The pen does not smell; e) Using an asbestos roof; f) There is good ventilation/air circulation; g) Simple shape; h) Individual pen model; and i) There is urine and feces processing. The design of cowshed that are in accordance with user desires include: a) There is a liquid waste drainage channel; b) There is a place for cow dung; c) The boundary wall in the pen is made of brick with a height of 100 cm; d) The poles in the pen are made of wood with a round shape; e) The slope of the floor is approximately 2 degrees so that the floor is dry; f) Using an asbestos roof; g) The design of a simple cage is as needed; h) There are food and drink containers for each cow; i) There is a place to tie but no divider for each cow; and j) There is a place to store liquid waste and a place for solid waste.